Plasmid Copy Number Determination by Quantitative Polymerase Chain Reaction - Anindyajati (Sci Pharm, 2016)
Recombinant therapeutic proteins are biopharmaceutical products that develop rapidly for years. Recombinant protein production in certain hosts requires vector expression harboring the gene encoding the corresponding protein. Escherichia coli is the prokaryote organism mostly used in recombinant protein production, commonly using a plasmid as the expression vector. Recombinant protein production is affected by plasmid copy number harboring the encoded gene, hence the determination of plasmid copy number also plays an important role in establishing a recombinant protein production system. On the industrial scale, a low copy number of plasmids are more suitable due to their better stability. In the previous study we constructed pCAD, a plasmid derived from the low copy number pBR322 plasmid. This study was aimed to confirm pCAD’s copy number by quantitative polymerase chain reaction (qPCR). Plasmid copy number was determined by comparing the quantification signal from the plasmid to those from the chromosome. Copy number was then calculated by using a known copy number plasmid as a standard. Two pairs of primers, called tdk and ori, were designed for targeting a single gene tdk in the chromosome and a conserved domain in the plasmid’s ori, respectively. Primer quality was analyzed in silico using PrimerSelect DNASTAR and PraTo software prior to in vitro evaluation on primer specificity and efficiency as well as optimization of qPCR conditions. Plasmid copy number determination was conducted on E. coli lysates harboring each plasmid, with the number of cells ranging from 10(2)–10(5) cells/μL. Cells were lysed by incubation at 95ºC for 10 minutes, followed by immediate freezing at −4°C. pBR322 plasmid with the copy number of ~19 copies/cell was used as the standard, while pJExpress414-sod plasmid possessing the high copy number pUC ori was also determined to test the method being used. In silico analysis based on primer-primer and primer-template interactions showed that both primer pairs were acceptable and were predicted to have good performance. Those predictions were in agreement with the in vitro test that gave a single band in the PCR product’s electropherogram and a single peak in DNA amplicon’s melting curve with a Tm value of 79.01 ± 0.11°C for the tdk primer and 81.53 ± 0.29°C for the ori primer. The efficiency of each primer was 1.95 and 1.97, respectively. The calculation result of pCAD’s copy number was 13.1 ± 0.3 copies/cell, showing that pCAD’s low copy number has been determined and confirmed. Meanwhile, it was 576.3 ± 91.9 copies/cell for pJExpress414-sod, in accordance with the hypothesis that pUC ori regulates the high copy number plasmid. In conclusion, the designed primers and qPCR conditions used in this study can be used to determine plasmid copy number for plasmids with pBR322 and pUC ori. The method should be tested further on plasmids harboring other type of ori.